Monocyte-derived exosomes upon exposure to cigarette smoke condensate alter their characteristics and show protective effect against cytotoxicity and HIV-1 replication - Haque, Sanjana (Sci Rep, 2017)
Smoking is known to exacerbate HIV-1 pathogenesis, especially in monocytes, through the oxidative stress pathway. Exosomes are known to alter HIV-1 pathogenesis through inter-cellular communication. However, the role of exosomes in smoking-mediated HIV-1 pathogenesis is unknown. In this study, we investigated the effect of cigarette smoke condensate (CSC) on the characteristics of monocyte-derived exosomes and their influence on HIV-1 replication. Initially, we demonstrated that CSC reduced total protein and antioxidant capacity in exosomes derived from HIV-1-infected and uninfected macrophages. The exosomes from CSC-treated uninfected cells showed a protective effect against cytotoxicity and viral replication in HIV-1-infected macrophages. However, exosomes derived from HIV-1-infected cells lost their protective capacity. The results suggest that the exosomal defense is likely to be more effective during the early phase of HIV-1 infection and diminishes at the latter phase. Furthermore, we showed CSC-mediated upregulation of catalase in exosomes from uninfected cells, with a decrease in the levels of catalase and PRDX6 in exosomes derived from HIV-1-infected cells. These results suggest a potential role of antioxidant enzymes, which are differentially packaged into CSC-exposed HIV-1-infected and uninfected cell-derived exosomes, on HIV-1 replication of recipient cells. Overall, our study suggests a novel role of exosomes in tobacco-mediated HIV-1 pathogenesis.